2015
DOI: 10.1002/wnan.1386
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of radiolabeled iron oxide nanoparticles for dual‐modality imaging

Abstract: Over the last decade, radiolabeled iron oxide nanoparticles have been developed as promising contrast agents for dual-modality positron emission tomography/magnetic resonance imaging (PET/MRI) or single-photon emission computed tomography/magnetic resonance imaging (SPECT/MRI). The combination of PET (or SPECT) with MRI can offer synergistic advantages for non-invasive, sensitive, high-resolution, and quantitative imaging, which is suitable for early detection of various diseases such as cancer. Here, we summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 70 publications
(169 reference statements)
0
47
0
Order By: Relevance
“…6 Some typical examples of using the inherent properties of inorganic nanoparticles for imaging include fluorescent emissions from quantum dots, 14 use of superparamagnetic iron oxide particles (SPIONs) as magnetic resonance imaging (MRI) contrast agents, etc. 15, 16 Alternatively, a suitable dye could be incorporated in the functionalized nanoparticles (such as silica nanoparticles) for PET/optical dual modality imaging. 17 When the nanoparticle is intended to be used for PET image guided drug delivery, it is prudent to choose a nanoplatform that ensures precise targeting, accurate dose delivery, and minimal toxicity in order to achieve maximal therapeutic efficacy.…”
Section: Pet Imaging Using Radiolabeled Nanoparticlesmentioning
confidence: 99%
“…6 Some typical examples of using the inherent properties of inorganic nanoparticles for imaging include fluorescent emissions from quantum dots, 14 use of superparamagnetic iron oxide particles (SPIONs) as magnetic resonance imaging (MRI) contrast agents, etc. 15, 16 Alternatively, a suitable dye could be incorporated in the functionalized nanoparticles (such as silica nanoparticles) for PET/optical dual modality imaging. 17 When the nanoparticle is intended to be used for PET image guided drug delivery, it is prudent to choose a nanoplatform that ensures precise targeting, accurate dose delivery, and minimal toxicity in order to achieve maximal therapeutic efficacy.…”
Section: Pet Imaging Using Radiolabeled Nanoparticlesmentioning
confidence: 99%
“…39 An analogous method for radiolabeling the clinically approved IONP Feraheme, coined heat-induced radiolabeling (HIR) by the authors, was demonstrated and may be a route for radiolabeling other metal oxide NPs with oxophilic tracers. 38 Omitting the IONP core, chelator free loading of 89 Zr was also observed using various molecular weight dextran NPs for PET/CT imaging of lymph node drainage as well as Cerenkov-guided tumor resection. 61 89 Zr was also loaded into highdensity liposome (HDL) for the tracking of tumorassociated macrophages (TAMs) in a murine breast cancer model.…”
Section: Pet Imagingmentioning
confidence: 96%
“…In another example, a ScFv anti-MET antibody fragment was dimerized to produce a cys-diabody and site specifically radiolabeled with 89 Zr using a DFO maleimide chelator. The anti-MET cys-diabody was rapidly screened from a phage display library to target nonsmall lung cell carcinoma, and other cancers that overexpress MET.…”
Section: Pet Imagingmentioning
confidence: 99%
“…[239] Traditional approach involving chelating agents such as DOTA [240243], NOTA [204, 244, 245], DTPA [246] and bis(dithiocarbamatebisphosphonate) (DTCPB) [247, 248] for 64 Cu and 68 Ga, and DFO for 89 Zr [249] has been reported in an array of differently designed and surface-functionalized SPIONs. For example, Thorek and coworkers reported a simple 89 Zr-labeled version of clinically relevant ferumoxytol with excellent toxicity and clearance profile, for high resolution investigation of lymphatic drainage in murine cancer models.…”
Section: Radiolabeled Nanomaterials For Cancer Theranosticsmentioning
confidence: 99%